PHYSIOTHERAPY MANAGEMENT IN PATIENTS POST SECTIO CAESAREA ERACS E.C OBLIQUE LOCATION RISK OF PLACENTA ACCRETA: CASE REPORT - Yasinta Relatami; W Wahyuni; Nurul Latifah (CV. Fahr Publishing, 2026)
Caesarean section (CS) is a commonly performed surgical procedure for childbirth, and its rate continues to increase globally, including in Indonesia. Women undergoing CS may experience a range of postoperative problems, including pain, restricted mobility, reduced functional capacity, and an increased risk of complications. Physiotherapy has an important role in facilitating recovery through the implementation of appropriate rehabilitation interventions. This case study was conducted to describe the physiotherapy management of a patient following cesarean section at PKU Muhammadiyah Gamping Hospital.. Pain intensity and functional performance were evaluated using the Numeric Rating Scale (NRS) and the Kenny Self-Care Index, respectively. The patient was a 28-year-old woman who reported pain around the surgical incision and difficulty with mobility following cesarean delivery. The physiotherapy program consisted of deep breathing exercises, free active exercises, pelvic floor exercises, and progressive mobilization training. Following two treatment sessions, tenderness decreased from a score of 3 to 2, while movement-related pain improved from a score of 4 to 2. Functional performance also improved across most domains, with many activities progressing from requiring moderate assistance to minimal assistance. However, no improvement was observed in upper-body dressing and several components of personal hygiene. Overall, the physiotherapy interventions contributed to reduced pain intensity and enhanced independence in functional activities during the early postoperative period.